GREEN STRATEGIES AND COMPETITIVE ADVANTAGE: THE MODERATING ROLE OF ENTREPRENEURIAL ORIENTATION - Erna Wati; Sheila Septiany; Ivone Ivone; Valene Fortuna Lim (Program Sarjana Manajemen Universitas Internasional Batam, 2026)
This study examines the effects of Green Intellectual Capital (GIC), Green Leadership (GL), and Strategic Leadership Capabilities (SLC) on Competitive Advantage (CA), and whether Entrepreneurial Orientation (EO) strengthens these effects. Data were collected through an online structured questionnaire from 163 professionals in environmentally oriented organizations using purposive sampling. The proposed model was tested using partial least squares structural equation modeling with reliability and validity checks, followed by hypothesis and interaction-effect testing. The results indicate that GIC, GL, and SLC have significant positive effect on CA. EO also significantly strengthens the effects of GIC, GL, and SLC on CA, suggesting that firms with stronger entrepreneurial orientation gain greater competitive returns from green intangible resources and leadership capabilities. This study offers managerial implications for enhancing competitiveness through targeted investments in green capabilities and entrepreneurial culture. Limitations include the single-country setting and cross-sectional survey design; therefore, future research should adopt longitudinal and multi-country designs, incorporate multi-source data, and explore additional mediating or moderating variables to provide deeper insights into the dynamic mechanisms linking green capabilities to competitive advantage.